ANALYSIS OF RESCUE RADAR NOISE IMMUNITY UNDER BROADBAND INTERFERENCE - Sytnik, O.; Masalov, S. (Radio physics and radio astronomy (Print), 2024)
Subject and Purpose. The subject of the research is the statistical characteristics of the signal, noise, and interference and their distribution functions. The emphasis is on exploring the properties of these elements and assessing their impact on algorithms designed to detect and identify the manifestations of human breathing and heartbeat during rescue operations. The work seeks comprehensive descriptions of broadband structural noise to develop optimum digital signal processing algorithms and ensure quicker and more reliable detection and identification of information signals during rescue missions. Method and Methodology. The analysis is grounded on the mathematical modeling method. The distribution function of correlation function peaks for a pseudo-noise signal is synthesized considering the first moments. The estimates derived from this distribution are used to assess the influence of broadband structural noise on the performance of algorithms for detecting and identifying radar signals. Results. In the most important band, where signal spectral components bear information on human breathing and heartbeat, estimates of the first four moments of a random process have been made to contribute to an appropriate model of fluctuating broadband structural noise. Analytical expressions of the function of structural interference distribution have been derived. A specific case focused on the interference represented by a phase-shift keyed signal with randomly alternating ones and zeros has been examined. Estimates of probabilities of false alarms and target misses have been calculated across various signal-to-noise ratios. Furthermore, a procedure to determine an optimal signal-detection threshold has been proposed. Conclusions. Analytical expressions of the distribution density of broadband structural interference have been derived. Quantitative estimates have been calculated to assess the impact this interference exerts on algorithms designed for detecting and recognizing radar information signals for rescuers. An adaptive procedure adjusting a target detection threshold as interference varies during the radar operation has been proposed.